2008
DOI: 10.1002/cncr.23502
|View full text |Cite
|
Sign up to set email alerts
|

Active surveillance for the management of prostate cancer in a contemporary cohort

Abstract: BACKGROUND.Active surveillance followed by selective treatment for men who have evidence of disease progression may be an option for select patients with early‐stage prostate cancer. In this article, the authors report their experience in a contemporary cohort of men with prostate cancer who were managed with active surveillance.METHODS.All men who were managed initially with active surveillance were identified through the authors' institutional database. Selection criteria for active surveillance included: pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
244
2
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(267 citation statements)
references
References 38 publications
11
244
2
10
Order By: Relevance
“…The number of positive cores, the tumour length (total or at any core) and the percent of cancer involvement at any core are predictive factors of tumour volume in RP specimens or biochemical failure after RP [8,[22][23]. The aim of our retrospective study was to compare the rate of misclassification associated with the use of 3 different biopsy criteria [13, [16][17]. For each criterion, we also tested the impact of PSA density on the number of men eligible and the risk of unfavourable disease [van den Bergh, Carter].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of positive cores, the tumour length (total or at any core) and the percent of cancer involvement at any core are predictive factors of tumour volume in RP specimens or biochemical failure after RP [8,[22][23]. The aim of our retrospective study was to compare the rate of misclassification associated with the use of 3 different biopsy criteria [13, [16][17]. For each criterion, we also tested the impact of PSA density on the number of men eligible and the risk of unfavourable disease [van den Bergh, Carter].…”
Section: Discussionmentioning
confidence: 99%
“…This may represent a bias, the target population for AS being larger than our restricted cohort. In this study, we tested current AS criteria which were internationally used or recently published [Carter,13,[16][17][18]. Our listing of AS criteria was not complete but provided a representative cohort of the men actually included in AS protocols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distinction is particularly important in that neither oncologic, nor quality of life, outcomes from patients assigned to observation in older randomized trials, [8,14], nor those identified in population-based registries as receiving conservative management, can be considered representative of those expected with contemporary active surveillance. Table 1 summarizes the published prospective experience with active surveillance, comprising more than 2900 patients [15][16][17][18][19][20][21][22][23]. These studies differ in terms of their eligibility and triggers for intervention.…”
Section: Active Surveillance Resultsmentioning
confidence: 99%
“…Previously referred to as "Watchful Waiting," this option has become structured with regular protocols including repeat prostatic biopsy and routine follow-up visits. Clearly this is not the best option for all patients, but recent data suggests that in a highly selected group of patients, active surveillance could provide a safe alternative to radical local therapy [8,9]. Caveats of this option include psychological distress, poor compliance, and possibly missing the window during which a cancer could be curable.…”
Section: Active Surveillancementioning
confidence: 99%